Repetitive Bending and Straightening of Sheet Metal: Effects on Microstructure and Mechanical Performance - ABDUL RAHMAN, AMIRUL RAIMI; Dr. MOHD NIZAM BIN KATIMON (Research Progress in Mechanical and Manufacturing Engineering, 2026)
This project investigates how the Repetitive Bending and Straightening (RBS) process affects the strength and internal structure of galvanized iron. The main goal was to compare the grain size and mechanical strength of the metal before and after undergoing 3 and 5 cycles of bending. To do this, the grain size was measured using a microscope, and the strength was tested using a tensile testing machine. The results showed that as the number of bending cycles increased, the grains (original) to 7.68 um inside the metal grew larger, increasing from 4.22 um (5 cycles). The tensile tests revealed that the original unbent metal was the strongest, with a maximum stress of 335.63 N/mm². Overall, the study concludes that this bending process made the material weaker and caused the grains to expand, rather than improving its strength.